The electronic book of educational training tasks on parallel programming based on the MPI 2.0 standard - Mikhail E. Abramyan (Современные информационные технологии и IT-образование, 2017)
We discuss one of approaches to the development of educational parallel software and describe the Programming Taskbook for MPI-2 (http://ptaskbook.com/ru/ptformpi2/), a courseware that includes 250 training tasks on various topics of MPI. We describe the history of its development, as well as give an overview of its task groups. Usage of the Programming Taskbook for MPI-2 at laboratory classes is illustrated by example of solving one of the training tasks. We also describe task groups related to such new features of MPI 2.0 interface as parallel input-output, remote memory access (one-sided communications), and dynamic creation of processes, and give formulations of some tasks from these groups. In addition, we discuss some features of the final task group devoted to parallel matrix algorithms.